Edição de genoma em Trypanosoma utilizando nucleases dedo de zinco e o sistema CRISPR/Cas9 - Gabriela de Assis Burle Caldas (2016)
Genetic manipulation in trypanosomatids is an essential tool to study these organisms, many of them are agents of important human and veterinary diseases. The introduction of exogenous DNA into the genome in any cell or the generation of a gene knockout requires a double strand break event (or DSB) and the repair of this DSB by homologous recombination (HR) or by other mechanisms. Two methods recently described in other organisms were tested in order to increase the efficiency of genetic manipulation in T. cruzi and T. brucei: the expression of zinc finger nucleases (ZFNs) and the CRISPR/Cas9 system. ZFNs are synthetic proteins having the ability to bind specifically to a DNA sequence and cause a DSB in a pre-defined region in the genome. CRISPR/Cas9 is part of the bacterial and archaea defense system against invasion by viruses and plasmids and requires a nuclease (Cas9) capable of cleaving a specific sequence in the presence of a small RNA (single guide RNA, or sgRNA) that recognizes the sequence targeted by complementarity. In this work we also tested the transfection system called nucleofection, which resulted in a 20 fold higher transfection efficiency compared with the electroporation protocol. To test a pair of ZFNs, epimastigotes of T. cruzi and T. brucei bloodstream forms expressing enhanced GFP (eGFP) were transfected with a plasmid encoding ZFNs designed to recognize and cleave the sequence of egfp. Because no loss in fluorescence and no detectable expression of ZFNs were observed by western or northern blots, we concluded that the constitutive expression of ZFNs directed to egfp could be toxic for these parasites. Expression of ZFNs under the control of tetracycline operator in T. brucei confirmed that the transient expression of this nuclease protein, although affecting parasites growth, resulted in increased transfection efficiency by up to 15 times. Since an appropriate system for etracycline-regulated expression was not available for T. cruzi, we generated a cell line expressing T7 RNA polymerase, and the tetracycline repressor, which was tested after transfection with a plasmid containing the renilla luciferase (Rluc) gene under the control of the tetracycline operator. However due to low levels of expression of the tetracycline repressor, high levels of Rluc expression were obtained before the addition of tetracycline. Aimed at testing a second pair of ZFNs, we expressed ZFNs that targets the gp72 gene, which was chosen because it’s knockout results in readily detectable phenotype with the flagellum detached from the parasite's body. Different from the result with ZFNs that targets egfp, transfection of epimastigotes constitutively expressing ZFNs that targets gp72 with a sequence containing the neomycin resistance gene flanked by gp72 sequences, resulted in G418 resistant population with 90% of cells with the gp72 knockout. PCR analyses showed that the neomycin resistance gene integrated into the gp72 locus. Similar results were obtained with the transfection of epimastigotes constitutively expressing Cas9 nuclease. To test the gp72 gene knockout using the CRISPR/Cas9 system this strain was transiently transfected with a circular plasmid containing gp72 and sgRNA scaffold sequence transcribed by the T. cruzi rRNA promoter. Following transient transfection with a plasmid containing the sgRNA sequence, a population in which approx. 1% of the cells showed the knockout phenotype of gp72 was obtained. Taken together, our results showed that the use of both nuclease resulted in a significant increase in the efficiency of gene knockout protocols for T. cruzi, thus constituting a valuable new tool for studies with this parasite.